2009
DOI: 10.1097/jto.0b013e3181add9c7
|View full text |Cite
|
Sign up to set email alerts
|

Second-Line Combination Chemotherapy with Docetaxel and Nedaplatin for Cisplatin-Pretreated Refractory Metastatic/Recurrent Esophageal Squamous Cell Carcinoma

Abstract: The combination chemotherapy of docetaxel and nedaplatin in the outpatient setting is well tolerated and useful as second-line chemotherapy for cisplatin-pretreated refractory metastatic/recurrent esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…Numerous cancers, including nasopharyngeal cancer, NSCLC, esophageal cancer, urothelial carcinoma and cervical cancer, have been reported to be effective to NDP-based chemotherapy in clinical studies (7)(8)(9)(10)(11)(12)(13). However, the majority of recent studies have focused on the therapeutic effect of NDP on esophageal cancer, although this type of cancer does not respond well to platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous cancers, including nasopharyngeal cancer, NSCLC, esophageal cancer, urothelial carcinoma and cervical cancer, have been reported to be effective to NDP-based chemotherapy in clinical studies (7)(8)(9)(10)(11)(12)(13). However, the majority of recent studies have focused on the therapeutic effect of NDP on esophageal cancer, although this type of cancer does not respond well to platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from response rates, the time to progression was short in most studies, being less than 4 months in 13 trials and being not stated in another five of 27 trials (Cuningham et al, 2008;Nakajima et al, 2008;Jin et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…Nedaplatin (NDP), which is a second-generation DDP analog, was developed by the Shionogi Pharmaceutical Company (Japan) in 1983, in order to provide a treatment with a level of effectiveness similar to that of DDP, but with decreased gastrointestinal and renal toxicities (12). A number of previous clinical studies have demonstrated the efficacy of NDP to be higher than that of DDP in patients with DDP-resistant lung cancer (13,14). Conversely, there are comparatively few in vitro studies to support the consensus.…”
Section: Introductionmentioning
confidence: 98%